Antecedents of social media usage intensity in the financial sector of an emerging economy: a Pls-Sem Algorithm - Amoah, John; Nutakor, Felix; Li, Jinke; Jibril, Abdul Bashiru; Sanful, Benjamin; Odei, Michael Amponsah (Management & marketing (Bucharest, Romania), 2021)
The purpose of this paper is to offer a critical understanding of the motivations and benefits of social media usage by small and medium financial enterprises with an empirical study from an emerging economy such as Ghana. Based on previous studies, the current study hypothesizes that customer-firm relationship, financial expectation, firm’s visibility and growth, and market share expectation drive social media usage intensity in the financial industry. Quantitative data was gathered from management and staff of SMEs, specifically, financial institution outlets (having social media channels i.e., Facebook, Instagram, YouTube, LinkedIn, etc.) was used to investigate the proposed conceptual framework. Using structural Equation Modelling, the research showed that customer-firm relationship, financial expectation, firm’s visibility and growth, and market share expectation are positively associated with social media usage intensity within the financial sector. Moreover, it was discovered that financial firms that offer physical products only were equally employing social media networks for marketing communication purposes based on cost-effective motives. At the same time, we found that SMEs are more likely to consider ‘market share expectation’ as a key motivation for social media adoption by the financial industry. The findings from this study have provided some solutions to potential research issues specific to strategic management practices. Limitations and future research directions are discussed in the concluding remarks.